1998
DOI: 10.1001/archpsyc.55.9.830
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Pursuit Eye Movements to Extraretinal Motion Signals

Abstract: Background: Although mounting evidence supports the idea that smooth pursuit abnormality marks the genetic liability to schizophrenia, the precise ocular motor mechanism underlying the abnormality remains unknown. Based on recent findings in schizophrenia, we hypothesize that subtle deficits in the ability to hold online and/or use extraretinal motion information underlie the pursuit abnormality in vulnerable individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Moreover, CD disturbances could reflect symptom vulnerability, rather being a proximal mechanism of psychosis. Consistent with that notion, abnormal predictive pursuit [23, 49, 50] (and smooth pursuit more generally [18]), as well as abnormal antisaccade error corrections [28] have also been observed in asymptomatic relatives of schizophrenia patients, suggesting a genetically mediated trait. Retrospective data showing CD abnormalities in high-risk individuals who eventually develop psychosis versus those who do not [51] would be particularly illuminating in this regard, but to our knowledge, these studies have not been performed.…”
Section: Evidence For Disturbed Oculomotor CD In Psychosismentioning
confidence: 79%
“…Moreover, CD disturbances could reflect symptom vulnerability, rather being a proximal mechanism of psychosis. Consistent with that notion, abnormal predictive pursuit [23, 49, 50] (and smooth pursuit more generally [18]), as well as abnormal antisaccade error corrections [28] have also been observed in asymptomatic relatives of schizophrenia patients, suggesting a genetically mediated trait. Retrospective data showing CD abnormalities in high-risk individuals who eventually develop psychosis versus those who do not [51] would be particularly illuminating in this regard, but to our knowledge, these studies have not been performed.…”
Section: Evidence For Disturbed Oculomotor CD In Psychosismentioning
confidence: 79%
“…As done in previous work (43), our a priori plan was to cast a broad net for ascertaining the presence of relevant elevated personality features by identifying individuals within one criterion of a cluster A (odd or eccentric) or cluster B (dramatic, emotional, or erratic) diagnosis. Given this project’s primary focus on identifying psychosis-related features, the psychotic-like features that characterize cluster A personality disorders were the primary traits of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The ramp-mask-ramp task used in the study has been described previously (Thaker et al, 1998;Sherr et al, 2002). Briefly, a foveal-petal step-ramp was presented followed by target motion in a horizontal plane, back and forth, at a constant velocity.…”
Section: Oculomotor Data Acquisitionmentioning
confidence: 99%
“…Here, we focus on data for 18.71/s trials in order to allow comparisons with the previously published report on leading saccades and smoking, which used a target speed of 161/s . In addition, a number of studies suggest that SPEM deficits are more reliably observed when higher target speeds are used (eg Abel et al, 1991;Clementz and McDowell, 1994;Clementz et al, 1995;Thaker et al, 1998)Fthis includes a report by Lencer et al (1999b) who found group differences in leading saccades only at higher target speeds (15 vs 301/s).…”
Section: Oculomotor Data Acquisitionmentioning
confidence: 99%